Women (re)writing Milton - Green, Mandy; Al-Akhras, Sharihan (New York, NY : Routledge, 2021)
"This volume of essays reconfigures the reception history of Milton and his works by bringing to the fore women reading, writing, and rewriting Milton, bringing together in conversation a range of voices from diverse historical, cultural, religious and social contexts across the globe and through the centuries"--
OCLC-licensed vendor bibliographic record.
Keywords: Milton, John, -- 1608-1674 -- Appreciation; Milton, John, -- 1608-1674 -- Influence; Literature -- Women authors -- History and criticism; LITERARY CRITICISM / Women Authors; SOCIAL SCIENCE / Gender Studies